Stress in women with Reproductive Failure - Bhandari, Sunita (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: The study aim to measure the level of stress in women with recurrent miscarriage and infertile women undergoing in-vitro fertilization treatment using psychological, endocrinological and immunological markers of stress. Methods: Group A（Recurrent Miscarriage Group, RM Group） of 20 women who had had at least three or more consecutive spontaneous abortions after negative biomedical diagnostic screening test; Group B (Infertility Group) of 40 infertile women undergoing in-vitro fertilization treatment after down-regulation with Gonadotropin-releasing Hormone (GnRH) agonist in a long protocol and Group C (Control Group) of 15 fertile women were asked to complete the stress questionnaires : the Perceived stress scale (PSS), the Fertility Problem Inventory (FPI), the Positive and Negative Scale (PANAS) and the SF-12 Health Survey. Blood samples were collected to measure natural killer (NK) cells and cortisol levels. Results: The score of stress questionnaires were significantly high in women with reproductive failure compared to fertile control group (p=0.023 for PSS; p=0.011 for FPI; p=0.013 for negative scale of PANAS) and the score of MCS from SF-12 Health Survey was significantly lower compared to control group (p=0.001). However, no significant differences were seen between women with RM and infertile women undergoing IVF treatment. Women with reproductive failure have increased number of peripheral NK cells compared to controls (p=0.000). No significant difference was found in the serum cortisol level between the women with reproductive failure and fertile women. Conclusions: Women with reproductive failure perceived higher levels of psychological stress. Level of stress in women with recurrent miscarriage is comparable to that of infertile women undergoing in-vitro fertilization treatment. Increased numbers of NK cells were found in the peripheral blood of women with reproductive failure.